Synthesis and characterization of TiO2-Fe for photocatalytic applications of domestic waste - Rahmadhani, Annisa; Nasution, Hasmalina; Prasetya, Prasetya; Dayumita, Novialis; Siregar, Sri Hilma (Acta Chimica Asiana, 2023)
Wastewater originating from household, industrial, and public places that contains materials can endanger human life and living things and disrupt environmental sustainability. Various methods have recycled domestic wastewater. One is through the photodegradation process utilizing ultraviolet light in the photocatalytic process. Inorganic materials are semiconductors with photocatalyst activity that can absorb photons and simultaneously carry out material interface transformation reactions. The research aimed to determine the effect of adding Fe metal dopants on TiO2 photocatalyst activity in simulated methylene blue and domestic waste treatment. The precursor used was TiO2 P25 Degussa Anatase. Fe dopant was added using the hydrothermal method with variations of 2%, 4%, and 6%. The XRD characterization results show that TiO2 has a high degree of crystallinity, so the overall process of electron diffusion and electron transfer in SSPT is higher to increase its efficiency. SEM-EDX characterization results show that TiO2-Fe particles are scattered in a spherical shape with a size of less than (<)100 nm and tend to agglomerate. Test results of simulated methylene blue (MB) waste with a UV-Vis spectrophotometer at variations in mass, concentration, pH, and time showed that the addition of doping could increase photocatalytic activity and optimum conditions at 6% (F6) were used in the analysis of parameters pH, COD and TSS of domestic wastewater. The pH value increased from 5 to 6, % COD degradation was 59.17%, and TSS was 23.07%. This research showed that TiO2-Fe was effective enough for domestic wastewater treatment.